Implementasi Perlindungan Hukum Keselamatan dan Kesehatan Kerja Terhadap Pekerja/Buruh di PT Sinar Semesta - Kenita Rizki Ayutama; Rahayu Subekti; Purwono Sungkowo Raharjo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Work accidents can be said to be a conflict in employment because they cause losses to workers and companies. Although the government has regulated the company's obligations in implementing occupational safety and health through various laws and regulations, in reality the effectiveness of the implementation of these regulations is still a problem, especially in terms of law enforcement in companies that have not fully implemented occupational safety standards according to applicable norms and provisions, one of which is at PT Sinar Semesta which is a metal casting company in Klaten Regency. This study aims to determine the regulations related to Occupational Safety and Health and the implementation of legal protection for Occupational Safety and Health at PT Sinar Semesta. This study uses an empirical legal research method. Based on the results of the study, it can be concluded that Occupational Safety and Health has actually been regulated in several laws and regulations. However, the implementation of legal protection for Occupational Safety and Health at PT Sinar Semesta has not been fully fulfilled because there are no health facilities specifically located in the company environment, the Occupational Safety and Health Management System has not been implemented, and the Occupational Safety and Health Development Committee has not been formed..